DIPRENYLATED XANTHONE FROM THE STEM BARK OF KANDIS GAJAH (Garcinia griffithii) - Elfita Elfita; Supriyatna Supriyatna; Husen H. Bahti; Dachriyanus Dachriyanus (Universitas Gadjah Mada, 2008)
A diprenylated xanthone, 1,5-dihydroxy-3-methoxy-4,7-diprenylxanthone (1) had been isolated the first time from the dichloromethane extract of the stem bark of Garcinia griffithii, together with 1,7-dihydroxyxanthone (2) and polyisoprenylated benzophenone, guttiferone I (3). The structure of these compounds were determined on the basis of spectroscopic data including UV, IR, 1H NMR, 13C NMR, HMQC, HMBC and COSY.